Implementation of the Cocoa Area Development Program Corporate-Based (Plant Integration Cocoa And Cow Livestock) In the Regency East Kolaka - Arafat, Arafat; Baso, Sudirman (IJBLE Scientific Publications Community Inc., 2023)
The agricultural sector is a mainstay in development in East Kolaka Regency, especially in cocoa and cow livestock commodities. The study's objective is to evaluate the impact of the corporate-based cocoa area development program (integration of cocoa plants and cow livestock) in the East Kolaka Regency. This study uses a qualitative descriptive analysis. The study results concluded that smallholder cocoa plantations have prospects in supporting the integrated farming model with cow livestock. Integrated farming strongly supports the pattern of commodity diversification (cocoa and cow livestock), which can support each other in both business sub-sectors. Cocoa farming does not affect increasing cocoa farming in each village. This is because the distribution of the proceeds from the sale of cow livestock is divided into groups, so the integration of cocoa and cow livestock is not carried out correctly.